Dampak Putusan Mahkamah Konstitusi Indonesia Nomor 65/PUU-XXI/2023 Terhadap Norma Sosial Kampanye Politik di Fasilitas Pendidikan Dan Gedung Pemerintah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The Constitutional Court of Indonesia Decision Number 65/PUU-XXI/2023 has significant implications for the social norms of political campaigns in educational facilities and government buildings. This research aims to explore the implications of the decision and the responses from various stakeholders. A literature review approach is employed, collecting and analyzing various sources including books, academic journals, and online resources related to law, politics, and education in Indonesia. The research findings indicate that the Constitutional Court's decision alters the landscape of political campaigns by allowing campaigning in educational institutions while still maintaining the ban in places of worship. Responses from various stakeholders, including academics, activists, and Civil Servants, highlight issues of neutrality, security, and education quality. The implications of this decision provoke intense debate concerning freedom of speech, institutional neutrality, and the balance between political participation and social stability. This research provides a deeper understanding of the political and legal dynamics in Indonesia, offering insights for the formulation of more effective policies in the context of political campaigns and education.